Linking Parkinson’s disease and melanoma: the impact of copper-driven cuproptosis and related mechanisms - Quan Wang; Yinghui Duan; Yu Xu; Hao Li; Yi Yang (npj Parkinson's Disease)
Abstract Patients with Parkinson’s disease (PD) exhibit an increased risk of melanoma, implying shared yet incompletely understood molecular mechanisms. This study aimed to delineate these common and distinct pathways by analyzing gene expression profiles from the Gene Expression Omnibus. A total of 90 differentially expressed genes (DEGs) were commonly regulated, while 173 DEGs exhibited divergent regulation between PD and melanoma. Protein-protein interaction analysis identified SNCA as a central node within a 21-protein network. LASSO regression revealed 13 hub genes (e.g., CCNB1, CCNH, CORO1C, and GSN) with high diagnostic accuracy (AUC >0.93) across both conditions. Gene set enrichment analysis implicated copper-induced cell death (cuproptosis) in PD neurons and melanoma cells, linking this process to hub genes. RT-qPCR confirmed increased SNCA expression during cuproptosis. Additional analyses identified macrophage involvement and WNT-β-catenin signaling as relevant. These findings suggest cuproptosis as a potential therapeutic target in PD and melanoma.